The ethnomethodology of metapragmatics in everyday interaction: A discussion note following Judith Bridges’s “Explaining ‘-splain’ in digital discourse” - Noy, Chaim (Language Under Discussion, 2022)
This discussion note is inspired by, and in turn expands on, a few themes and threads laid out in Judith Bridges’s “Explaining ‘-splain’ in digital discourse”. The note stresses the focus and contribution linguistic anthropologists have made to understanding various types of indexical meaning-making practices, and the order of indexicality. This discussion note also briefly details the affordances of the word “explain” and the suffix “x-plain”, which may account for why this suffix, and not others, has come to be used so frequently.